Стратегія як інструмент забезпечення економічного розвитку держави - Вініченко, Ігор Іванович; Vіnіchenko, Igor; Мостова, А. Д.; Mostova, A. (Дніпровський державний аграрно-економічний університет, 2016)
Розглянуто теоретичні підходи до стратегічного планування та поняття стратегії. Досліджено особливості зарубіжного та вітчизняного досвіду формування економічної стратегії на загальнодержавному рівні. Проаналізовано теоретичні і методологічні підходи до розробки стратегій економічного, соціального та екологічного розвитку національних економік. Виявлено основні недоліки існуючої системи планування та прогнозування економічного розвитку, характерні для українських стратегій. Сформульовано сутність стратегії на загальнодержавному рівні, її об’єкт і суб’єкт, стратегічні цілі, напрями, завдання та результати. Представлено позиції провідних науковців щодо визначення державного стратегічного планування та стратегії економічного розвитку країни. Розкрито необхідність розробки стратегії продовольчої безпеки у складі економічної стратегії держави. Надано рекомендації щодо вдосконалення теоретичних і методологічних підходів до розробки стратегії економічного розвитку в цілому і, зокрема, продовольчої безпеки на державному рівні. The article deals with the theoretical and methodological approaches to strategic planning and understanding the concept of strategy. The main problems, associated with the strategic planning of economic development at the state level, are revealed. The features of foreign and domestic experience of economic strategy formation at the national level are researched. Theoretical and methodological approaches to creating strategies of economic, social and environmental development of national economies are analysed. The basic shortcomings of the existing system of planning and forecasting of economic development of typical Ukrainian strategies are identified.The essence of economic strategy at the national level, its object and subject are formulated. The strategic goals, directions, objectives and results of the strategy are determined. The positions of leading scientists determining the state strategic planning and economic development strategy of the country are presented. The tasks of the state economic strategy of Ukraine are identified in the research. The need for effective strategic economic policy is approved for implementation of the state strategy.The need of forming the strategy of food security as a part of the economic strategy of the state is revealed. The recommendations for improving the methodological and methodical approaches to develop the economic strategies in general and the food security strategies in particular at the national level are proposed.
Strategy as a tool for economic development of the state
Keywords: економічна стратегія держави; economic strategy of the state; стратегічна мета; the strategic objective; стратегічні напрями; strategic directions; цілі й завдання; goals and objectives; стратегічні результати; strategic results; стратегія продовольчої безпеки; the strategy of food security